Design Application And Its Economic Analysis Of Quick Tempe Technology In Pamulang - Theofilus Christian; Tabligh Permana; Stacia Andani Fortunata; Della Rahmawati; Irvan Setiadi Kartawiria; Maria Dewi Puspitasari Tirtaningtyas Gunawan Puteri (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2019)
Ipeh Tempe House in Pamulang was unable to fulfill their demand for more tempe production due to their limitation to expand the production using their own method. Quick tempe technology is a tempe production method with less production time than the common production method. Implementation of this method could increase production capacity without further infrastructure investment. Prior the implementation, the quick tempe technology was adjusted with the current production method in Ipeh Tempe House. Adjustment made was especially in the proper ratio of starter addition, the proper GDL addition method, and the maximum number of back slopping. The scheduling models of GDL tempe production method in Ipeh tempe house were designed to increase the production capacity of Ipeh tempe house, and the economic analysis was also performed to see whether the schedules suggested was feasible to do in real life, by calculating the profits generated by the schedules, and all of them were more profitable than normal method. To conclude, the procedure can create more batches, while giving more profit, but validation for the procedure and calculation is still needed to be done, other thing such as back slopping sensory test is also need to be done.